Prevalence of Different Types of Integrative Conjugative Element SXT/R391 Encoding Multiple Antibiotic Resistance Among Clinical Strains of Cholera Agent - D. A. Rybal’chenko; E. Yu. Shchelkanova; Yu. V. Lozovsky; A. V. Fedorov; N. I. Smirnova (Проблемы особо опасных инфекций, 2022)
The aim of the work was to study the prevalence of different types of SXT element with different composition of antibiotic resistance genes among clinical strains of the El Tor cholera pathogen isolated in Russia, Ukraine and cholera-endemic countries in Asia and Africa.Materials and methods. The subject of the study was 27 strains and nucleotide sequences of 77 strains of Vibrio cholerae El Tor available from the NCBI GenBank. The structure of the SXT element and its type were determined using the Mauve and BLAST v.2.9.0 programs. Phylogenetic relations of strains with different types of SXT were identified using Snippy v.4.6.0 and MrBayes v.3.2.7 software. Assessment of strain sensitivity to antibiotics was carried out in accordance with Methodological Regulations 4.2.2495-09.Results and discussion. Two types of SXT element (ICEVchInd5 and ICEVchBan9) have been identified among the studied strains from Russia and Ukraine, which have different composition of antibiotic resistance genes: floR, strAB, sul2, dfrA1 and floR, tetAR, strAB, sul2, dfrA1, respectively. At the same time, the studied strains from Asia and Africa contain five types of SXT: ICEVchInd5, ICEVchBan9, ICEVchBan5, SXTTET, ICEVchInd5ΔVRIII, which differ in size and/or composition of resistance genes. Of these, the last three have not been found in Russia and Ukraine. Due to the high level of genomic diversity of SXT in the population of V. cholerae in endemic regions, there is a risk of importation of cholera pathogen strains with altered resistance to antibiotics into Russia. Phylogenetic relations of 76 strains with different SXT types and different alleles of the ctxB gene encoding the B subunit of cholera toxin have been assessed based on SNP analysis. A close phylogenetic relation between strains with the same type of SXT isolated in Russia and Asian countries has been demonstrated, which confirms the importation of the causative agent of cholera with multiple resistance to antibiotics from this region and the need for constant monitoring of the sensitivity of V. cholerae to antimicrobial drugs.